Homeostatic Plasticity Mediated by Rod-Cone Gap Junction Coupling in Retinal Degenerative Dystrophic RCS Rats - Hou, Baoke; Fu, Yan; Weng, Chuanhuang; Liu, Weiping; Zhao, Congjian; Yin, Zheng Qin (Frontiers in Cellular Neuroscience, 2017)
The rod-cone gap junction coupling regulated by the circadian clock, is a novel form of homeostatic plasticity to regulate retinal excitability based on network activity. Using tracer labelling and ERG recording in the retinae of control and retinal degenerative dystrophic RCS rats, we show that the rod-cone gap junction coupling is regulated by the circadian clock through modulation of the phosphorylation of the melatonin synthetic enzyme arylalkylamine N-acetyltransferase (AANAT). However, in dystrophic RCS rats, AANAT is constitutively phosphorylated, leading to rod-cone gap junctions open. The b/a-wave ratio reveals that dystrophic RCS rats show stronger synaptic strength between photoreceptors and bipolar cells, possibly due to rod-cone gap junction opening. These results suggest that this electric synaptic plasticity is increased during the day, allowing the cone signals to pass to the remaining rods and propagate to rod bipolar cells, thereby partially compensating for the weak visual input caused by loss of rods.